Effect of Soil Type on Lateral Displacement of Reinforced Concrete Building - Dermawan Zebua; Leonardus Setia Budi Wibowo (POLITEKNIK NEGERI JAKARTA, 2022)
As has happened in various cases of earthquakes, the impact caused by each earthquake event varies, because the earthquake shaking that occurs on the ground is not only influenced by the distance and strength of the earthquake, but also by local soil conditions which are related to the amplification phenomenon. earthquake waves are influenced by the type and thickness of the soil/sediment layer above the bedrock. Reinforced concrete storey buildings are designed to withstand both vertical and horizontal loads. The taller the building, the greater the lateral load that will be received by the building structure. In the design of earthquake-resistant structures, the inelastic behavior of the structure is highly expected for the occurrence of earthquake energy dispersion during both moderate and strong earthquakes. In earthquake-prone countries such as Indonesia, it is required to comply with applicable national standards and the structure can still function and be safe from earthquakes affected by the earthquake. The purpose of this study was to determine how much influence the type of soil has on the lateral displacement of a 10-story reinforced concrete building using shear walls in accordance with earthquake building regulations (SNI 1726, 2019) and loading (SNI 1727, 2020). The results obtained that soft soil types have the largest displacement value with a value of 91,831 mm and hard rock soil types have the smallest displacement value with a value of 44,114 mm.